2022
DOI: 10.3390/ijms23063327
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory miRNAs in Cardiovascular and Alzheimer’s Disease: A Focus on Copper

Abstract: Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), are key regulators of differentiation and development. In the cell, transcription factors regulate the production of miRNA in response to different external stimuli. Copper (Cu) is a heavy metal and an essential micronutrient with widespread industrial applications. It is involved in a number of vital biological processes encompassing respiration, blood cell line maturation, and immune responses. In recent years, the link between deregulation of miRNAs’ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 128 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…Transcription factors regulate miRNA production in response to external stimuli and are especially active in the brain 75 . Under ischemia and hypoxia, transcription factors inactivate neurons within a few minutes, causing serious brain dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors regulate miRNA production in response to external stimuli and are especially active in the brain 75 . Under ischemia and hypoxia, transcription factors inactivate neurons within a few minutes, causing serious brain dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Copper is an essential mineral element for the human body which can participate in physiological processes such as erythropoiesis, immune function and resistance to oxidative stress damage, energy production, glucose metabolism and neuropeptide synthesis 14,15 . However, in recent years, a large number of studies have found that high exposure to copper may be associated with an elevated risk of developing a variety of chronic diseases, such as coronary heart disease, stroke and Alzheimer's disease 16–19 . Notably, the association between copper and diabetes has been widely recognized.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, in recent years, a large number of studies have found that high exposure to copper may be associated with an elevated risk of developing a variety of chronic diseases, such as coronary heart disease, stroke and Alzheimer's disease. [16][17][18][19] Notably, the association between copper and diabetes has been widely recognized. A recent meta-analysis by Qiu et al found that diabetic patients carried higher levels of copper than healthy individuals.…”
mentioning
confidence: 99%
“…Copper (Cu) is essential heavy metal but excess of copper in human body is lifethreatening (Irawati et al, 2019;Irawati & Tahya, 2020Nurlaila et al, 2021). Several studies have indicated that an imbalance in copper levels can contribute to Alzheimer's disease and cardiovascular disease (Sacco et al, 2022). Copper is also toxic to amphibians, fish and invertebrates.…”
Section: Introductionmentioning
confidence: 99%